Primary and Revision Rhinoplasty: A Single Surgeon Experience and Patient Satisfaction. Issue 9 (13th September 2021) - Suresh, Rishi; Doval, Andres F.; Newstrom, Emily; Pham, Truce; Alford, Eugene L.
Abstract : Background: There is minimal information describing the common characteristics among patients seeking primary/revision rhinoplasty. Success is traditionally interpreted from the surgeon's viewpoint, without considering the patient's perspective. The study's aims were to (1) identify/compare anatomic and functional characteristics commonly found in patients seeking primary and revision rhinoplasties; (2) assess patient satisfaction using a survey; and (3) explore whether graft choice (auricular cartilage versus rib cartilage) affects patient satisfaction and outcome in revision rhinoplasty. Methods: A retrospective review of all rhinoplasties by a single surgeon from June 2016 to January 2020 was performed, focusing on preoperative anatomic/functional characteristics and operative interventions performed. A survey was then used to assess patient satisfaction. Finally, survey outcomes were compared between patients who received auricular and rib cartilage grafts in revision rhinoplasty. Results: A total of 102 rhinoplasties (53 primary and 49 revisions) were included. Primary rhinoplasties were noted to have more patients with "big" noses ( P = 0.015) or humps ( P < 0.010). Patients undergoing revision rhinoplasties more commonly exhibited middle vault collapse ( P = 0.022). The survey response rate was 60%. Revision rhinoplasty patients had a higher incidence of dissatisfaction with their outcome Conclusions: Several features among patients seeking revision rhinoplasties could have been created in the primary operation. The rhinoplasty surgeon should be careful to not introduce new issues or create worse deformities than those seen following the initial operation. Survey-based outcome analysis demonstrated that revision rhinoplasty patients are more likely to have a greater rate of dissatisfaction following their operation.